The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1073/pnas.0611224104
|View full text |Cite
|
Sign up to set email alerts
|

The changing carbon cycle at Mauna Loa Observatory

Abstract: The amplitude of the CO2 seasonal cycle at the Mauna Loa Observatory (MLO) increased from the early 1970s to the early 1990s but decreased thereafter despite continued warming over northern continents. Because of its location relative to the large-scale atmospheric circulation, the MLO receives mainly Eurasian air masses in the northern hemisphere ( atmospheric circulation ͉ atmospheric CO2 seasonal cycle ͉ terrestrial carbon sinks ͉ continental droughts T he time series of CO 2 at Mauna Loa Observatory (MLO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
102
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 31 publications
10
102
0
Order By: Relevance
“…The extent to which snow accumulation can explain variations in greenness varies with elevation, reaching a maximum in the water-limited midelevations, between 2,000 and 2,600 m. In situ measurements of carbon uptake and snow accumulation along an elevational transect in the region confirm the elevation dependence of this relationship. We suggest that mid-elevation mountain forest ecosystems could prove particularly sensitive to future increases in temperature and concurrent changes in snow accumulation and melt.Recent studies have documented a shift from energy to water limitation across forested ecosystems of western North America 5,6 . This transformation has reversed the response of these ecosystems to increases in temperature where before the early 1990s increases in air temperature increased terrestrial carbon uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which snow accumulation can explain variations in greenness varies with elevation, reaching a maximum in the water-limited midelevations, between 2,000 and 2,600 m. In situ measurements of carbon uptake and snow accumulation along an elevational transect in the region confirm the elevation dependence of this relationship. We suggest that mid-elevation mountain forest ecosystems could prove particularly sensitive to future increases in temperature and concurrent changes in snow accumulation and melt.Recent studies have documented a shift from energy to water limitation across forested ecosystems of western North America 5,6 . This transformation has reversed the response of these ecosystems to increases in temperature where before the early 1990s increases in air temperature increased terrestrial carbon uptake.…”
mentioning
confidence: 99%
“…Recent studies have documented a shift from energy to water limitation across forested ecosystems of western North America 5,6 . This transformation has reversed the response of these ecosystems to increases in temperature where before the early 1990s increases in air temperature increased terrestrial carbon uptake.…”
mentioning
confidence: 99%
“…In addition to the trend [1][2][3] and the annual cycle [4][5][6][7][8][9], atmospheric CO 2 also demonstrates a lot of intra-seasonal [10,11] and inter-annual variability [12][13][14][15]. During the pre-satellite era, CO 2 analyses mainly utilized in-situ CO 2 measurements to investigate CO 2 variability, which is limited in space.…”
Section: Introductionmentioning
confidence: 99%
“…Large GPP means more photosynthesis, thus more CO 2 uptake from biosphere and less CO 2 in the atmosphere. Using CO 2 data over Mauna Loa, Buermann et al [8] found that the decline in the CO 2 seasonal cycle amplitudes since the early 1990s is related to reductions in the carbon sequestration as responses to severe droughts and changes in the atmospheric circulation. Norman et al [24] measured soil surface CO 2 fluxes at three sites and found that the soil surface CO 2 fluxes are sensitive to the drought and temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation